Measuring the extent to which people is 'left behind' in multidimensional poverty in European countries - García-Pardo, Francisca; Bárcena-Martín, Elena María; Pérez-Moreno, Salvador Jesús (My University, 2021)
In this study we use a fuzzy approach to measure the degree to which an individual is left behind in terms of multidimensional poverty according to the AROPE framework in 2017 from a comparative European. We evince that those countries with a greater proportion of individuals at risk of poverty or social exclusion also hold left-behind people to a larger extent. Nevertheless, there are singular cases that would require special attention, such as Finland, the United Kingdom and Ireland, where the problem of leaving people behind is relatively high in comparison to their levels of AROPE. Our results also reveal that over the post-crisis period 2013-2017 most countries –although with some exceptions, such as Luxembourg– reduced the degree to which people are left behind, and the people most left behind benefitted in a greater proportion from economic prosperity. Our approach allows comparing information according to certain socioeconomic characteristics of the population in order to highlight systematic disadvantages that leave some segments of society behind and to help policymakers prioritise interventions to accelerate progress among the furthest behind.
Keywords: Pobreza; Exclusión social; Multidimensional poverty; Fuzzy logic; AROPE